Predictors and morphological properties of culprit healed plaques in patients with angina pectoris. Issue 12 (7th September 2022) - Yao, Hongying; Guo, Qianyun; Cheng, Yujing; Zhu, Tianyu; Ma, Qian; Zhou, Yujie
Abstract: Background: Plaque healing may serve a vital function in the natural progression of atherosclerotic disease. This study sought to investigate predictors and morphological characteristics of healed plaque (HP) among angina pectoris (AP) patients. Methods: Patients who presented with AP and received preintervention optical coherence tomography (OCT) imaging were consecutively selected for this single‐center retrospective observational study. Patient's demographic and clinical information was collected from the hospital's electronic medical records. Coronary angiograms and OCT images were compared via offline software. Results: A total of 390 patients were chosen as the final study population. HP was identified in 186 patients (47.7%) and was relatively less in cases of unstable angina pectoris (UAP) than in stable angina pectoris (SAP) (89/233 [38.2%] vs. 97/157[61.8%]). The HP group had greater prevalence rates of previous myocardial infarction and SAP and higher levels of triglycerides and uremia (median, 1.67 vs. 1.31 mmol/L [ p  = .01] and 364.22 ± 91.80 vs. 341.53 ± 77.64 µmol/L [ p  = .01], respectively). Using multivariate analysis, SAP and long lesion length were shown to be stand‐alone indicators of HP. HP presented with more severe stenosis as well as a longer lesion length and had more vulnerable and more complex features. In HP lesions, UAP patients had more plaque ruptures and thrombosis, whereas SAP patients had lower uric acid levels and more multiple HPs(≥3 HPs). Conclusion: Clinical presentation of SAP and long lesion length were strong predictors for HP in patients with AP. Patients with HP presented with more severe stenosis, longer lesion lengths, greater inflammation, and vulnerability.